Using Vocal Production to Improve Long-Term Verbal Memory in Adults with Intellectual Disability. Issue 5 (September 2021) - Icht, Michal; Ben-David, Nophar; Mama, Yaniv
Individuals with intellectual disability (ID) typically show weak long-term memory (LTM) skills. Understanding verbal LTM processes and searching for effective mnemonics in this population is important, to improve intervention programs. The current study aimed to assess verbal LTM abilities of adults with mild ID of mixed etiologies, and to offer a simple memorization technique based on vocal production. Participants ( n = 55) learned lists of different study materials (images of familiar and unfamiliar objects, written words, and sentences) by vocal production (saying or reading aloud) or by no-production (looking, listening, or reading silently). Memory tests followed. Better memory was found for vocally produced images of familiar objects, written words, and sentences. The results show that adults with mild ID can benefit from the relative distinctiveness of items at study. Hence, vocalization may be used in educational and therapeutic contexts for this population, improving memory performance.